What isn't measured isn't done – eight years with no progress in Aboriginal and Torres Strait Islander adult influenza and pneumococcal vaccination. (16th October 2019) - Webster, Fleur; Gidding, Heather; Matthews, Veronica; Taylor, Richard; Menzies, Robert
Abstract: Objectives: To describe and compare vaccination coverage for Aboriginal and Torres Strait Islander (hereafter referred to as Indigenous) adults in 2004–05 and 2012–13, including the impact of national vaccination funding initiatives. Methods: National Aboriginal and Torres Strait Islander Health cross‐sectional surveys – 2004–05 (n=5, 757) and 2012–13 (n=5, 482) – were compared. Self‐reported influenza and pneumococcal vaccination coverage among Indigenous adults was analysed by age, remoteness, gender and risk factor status. Results: Influenza vaccination coverage among Indigenous adults in 2004–05 and 2012–13 remained low. While coverage increased for those aged 18–49 years from 23% to 29%, it declined for those aged ≥65 years from 84% to 74%. For remote areas, influenza coverage among those aged 50–64 years declined from 76% to 66%. Pneumococcal vaccination coverage remained very low and declined across all age groups in 2004–05 and 2012–13 (50–64 years: 30% to 23%). For remote areas, pneumococcal coverage declined among those aged 50–64 years from 52% to 32%. Conclusions: Indigenous adult vaccination coverage for influenza and pneumococcal disease remains unacceptably low. Between 2004–05 and 2012–13, declines occurred in pneumococcal vaccination coverage across all age groups ≥18 years. Despite national funding of influenza vaccine in 2010, there was no increase in influenza coverage, except for the 18–49‐year age group. Implications for public health: Current approaches to promote, deliver and monitor vaccination of Indigenous adults are inadequate.